1996
DOI: 10.1017/s135772980001434x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ovulation rate and late embryonic mortality in ewe lambs and ewes and the rôle of late embryo loss in ewe lamb subfertility

Abstract: An investigation was conducted to compare late embryonic losses in ewe lambs and ewes and to determine the effect of inducing embryonic mortality on day 15 of pregnancy on reproductive function in ewe lambs. Ovulation rate and embryo survival were determined, at 15 and 30 days after mating, in a total of 83 ewe lambs and 67 ewes. Ovulation rate was lower, at spontaneous oestrus, in ewe lambs (1-07) than in ewes (1-25; P < 0-05). There was no difference in embryo survival at day 15, as 79% of ewe lambs and 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…Sheep producers generally avoid breeding young females during adolescence because relative to adults, they have an inferior reproductive performance characterised by a variable onset of puberty and short first breeding season, low ovulation rate, failure to be mated, fertilisation failure and high embryo loss (Beck et al 1996, Kenyon et al 2014, Edwards et al 2016. The approach developed at the Rowett Institute bypasses many of these issues by using assisted conception procedures to synchronise breeding and establish singleton pregnancies in peripubertal adolescent ewes of equivalent age (~7.5 months), and standardised live-weight and adiposity at conception.…”
Section: Adolescent Sheep Paradigms: Approachmentioning
confidence: 99%
“…Sheep producers generally avoid breeding young females during adolescence because relative to adults, they have an inferior reproductive performance characterised by a variable onset of puberty and short first breeding season, low ovulation rate, failure to be mated, fertilisation failure and high embryo loss (Beck et al 1996, Kenyon et al 2014, Edwards et al 2016. The approach developed at the Rowett Institute bypasses many of these issues by using assisted conception procedures to synchronise breeding and establish singleton pregnancies in peripubertal adolescent ewes of equivalent age (~7.5 months), and standardised live-weight and adiposity at conception.…”
Section: Adolescent Sheep Paradigms: Approachmentioning
confidence: 99%
“…A subfertilidade em cordeiras é uma das causas de redução da produtividade do rebanho. Embora a taxa de fertilidade sofra influência de vários fatores, 20 a 40% das cordeiras falham em produzir seu primeiro cordeiro (Davies & Beck, 1993;Beck & Davies, 1994;Beck et al, 1996).…”
unclassified
“…Ewe lambs experience a decrease in overall fertility attributed to lower ovulation rates and higher embryonic mortality rates compared to mature ewes. Ewe lambs have a lower ovulation rate compared to mature ewes as demonstrated in Romney and Romney cross (1.14 v 1.82 and 1.44 v 1.84; Mulvaney et al, 2013) Clun forest (1.07 v 1.25; Beck et al, 1996), and Galway (1.51 v 3.07) breeds (Quirke and Hanrahan, 1977). Additionally, lowland Clun Forest ewes experience a subsequent increase in ovulation rate as they increase in age (ewe lambs= 1.15 v yearlings= 1.55 v two year olds= 1.75; Forrest and Bichard, 1974).…”
Section: Ovulation Ratesmentioning
confidence: 95%
“…Prenatal mortality rates are elevated in ewe lambs compared to mature ewes due to a decrease in ova viability. Research has shown that there is no difference in embryonic survivability between ewe lambs and mature ewes (79 v 80%) on embryonic day 15, but by embryonic day 30, the amount of ewe lambs containing viable fetuses decreased significantly compared to mature ewes (69 v 88% respectively; Beck et al, 1996). This indicates that there is a higher rate of embryonic loss by 30 days of pregnancy in ewe lambs.…”
Section: Prenatal and Perinatal Mortalitymentioning
confidence: 99%
See 1 more Smart Citation